ANALISIS RASIO PROFITABILITAS TERHADAP LABA STUDI KASUS PADA MEUBEL CHANDRA JAYA DI KOTA SORONG - Ferdinando Solissa; Yerrynaldo Loppies (Yayasan Akrab Pekanbaru, 2019)
This study aims to look at profitability in the furniture business Victory in the city of Sorong. The data used are quantitative data, namely financial statements including the balance sheet, and income statement for 2016 to 2018. This study uses profitability ratio analysis techniques.The results show that the operating profit margin proves that the comparison of data in 2017 increased more in the previous year for operating profit in 2017 with the yield in rupiahs of 73 rupiahs, while in 2018 there was a significant increase from the previous year for operating profits namely obtaining the result in rupiah units is 78 rupiahs. For net income, if the comparison of yield data in rupiahs in 2017 also increased from the previous year in 2016 in net income in rupiahs, it earned 7 rupiahs while in 2018 the same results were in 2017 For ROI results prove that if the comparison of 2017 results data increased ROI from the previous year in 2016 by obtaining results in units of rupiah that is 197 rupiahs while in 2018 experienced a significant decrease by obtaining results for ROI in units of rupiah that is 163 rupiahs. litas in the Chandra Jaya furniture business in Sorong city from 2016 and 2018 there was an increase in operating profit margins and net income, although ROI was still not visible in 2018, as was the case in 2017, so this business capability was needed to increase its profits.